ADOPSI TEKNOLOGI BUDIDAYA TANAMAN KEDELAI DI TINGKAT PETANI KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA; I DEWA GEDE SUARTHA; I PUTU CAKRA PUTRA ADNYANA (Universitas Mahasaraswati K. Mataram, 2022)
Soybean is one of the horticultural crops developed in Indonesia, because of its benefits, besides being able to be consumed directly, it can also be used as raw material for home industries and large industries such as tempeh, tofu, soy sauce, soy milk and others. The various benefits of soybeans are not supported by sufficient availability, so that until now Indonesia is still exporting soybeans. This study aims to determine the soybean cultivation system implemented by farmers in West Lombok Regency. This research is a descriptive study, which was carried out in Gerung Village, Gerung District and Kediri Village, Kediri District, West Lombok Regency. Determination of the location in a stratified (two-stage) selection mechanism, is first to choose the sub-district with the largest soybean planting area, then from the selected sub-district the village with the largest soybean planting area is also determined. The number of respondents who were taken was done by non-random sampling, each village was 30 respondents, so that the total number of respondents was 60 people. The data used in this study are qualitative data and quantitative data, with data collection techniques using interviews, observations and documentation, and data collection tools using questionnaires.The results of the study indicate that the farming system adopted by the respondent farmers has not been fully implemented in accordance with the recommendations. This is related to the different socio-economic conditions of farmers.